Mortality and functional outcome after surgical evacuation of traumatic acute subdural hematomas in octa- and nonagenarians - Younsi, Alexander; Fischer, Jessica; Habel, Cleo; Riemann, Lennart; Scherer, Moritz; Unterberg, Andreas; Zweckberger, Klaus (European journal of trauma and emergency surgery, 2021)
The incidence of acute subdural hematomas (aSDH) is rising. However, beneficial effects of surgery for the oldest aSDH patients remain unclear. We hence describe the postoperative outcome of octa- and nonagenarians with aSDH in comparison to a younger patient cohort.
Published: 27 June 2020
Gesehen am 06.12.2021